Emotional user experience in web design : the Kansei Engineering approach / Anitawati Mohd Lokman - Mohd Lokman, Anitawati (2009)
The use of the Internet has become an essential part of our everyday lives. People surf the website with various purpose to accomplish their personal goals. Inline with the thriving growth in the use of website, research in website design has expanded the focus from functionality and usability to the full range of human experience. In recent years, Human Computer Interaction (HO) issues related to web applications have shifted its focus to address emotional aspect of website design. This is mainly due to the evolution of website functions from conveying information to the extent of providing persuasive engagement with visitors through the lively process of perception, judgment and action. Over the Internet, visitor's perception of websites significantly affects their browsing behaviours and purchase decisions. With its nature of unlimited availability, online businesses are exposed to vast competition. Hence, an online business need to offer a website that could capture visitor's attention at first sight and persuade them to stay longer on the website, to win over competitor. Supported by previous literature involving studies on user experience, this research argue that to motivate stickiness to website, the website must be able to cultivate emotional engagement and elicit positive user experience. To enable the development of such website, the knowledge of how design elements influence emotion must be pursued so that we could engineer the emotion into a website design. This research was performed to systematically engineer the aspect of emotional user experience in Website UID. The research formulated its research framework based on Kansei Engineering (K.E.) methodology.